Mesenchymal stem cells suppress neuronal apoptosis and decrease IL-10 release via the TLR2/NFκB pathway in rats with hypoxic-ischemic brain damage. Issue 1 (December 2015) - Gu, Yan; Zhang, Yun; Bi, Yang; Liu, Jingjing; Tan, Bin; Gong, Min; Li, Tingyu; Chen, Jie
Abstract Background Hypoxic–ischemic brain damage (HIBD) is a major cause of infant mortality and neurological disability in children. Many studies have demonstrated that mesenchymal stem cell (MSC) transplantation facilitates the restoration of the biological function of injured tissue following HIBD via immunomodulation. This study aimed to elucidate the mechanisms by which MSCs mediate immunomodulation via the key effectors Toll-like receptor 2 (TLR2) and interleukin-10 (IL-10). Results We showed that TLR2 expression in the brain of HIBD rats was upregulated following HIBD and that MSC transplantation suppressed the expression of TLR2 and the release of IL-10, thereby alleviating the learning-memory deficits of HIBD rats. Following treatment with the specific TLR2 agonist Pam3CSK4 to activate TLR2, learning-memory function became further impaired, and the levels of nuclear factor kappa B (NFκB) and Bax expression and IL-10 release were significantly increased compared with those in HIBD rats that did not receive Pam3CSK4.In vitro, we found that MSC co-culture downregulated TLR2/NFκB signaling and repressed Bax expression and IL-10 secretion in oxygen and glucose deprivation (OGD)-injured adrenal pheochromocytoma (PC12) cells. Furthermore, NFκB and Bax expression and IL-10 release were enhanced following Pam3CSK4 treatment and were decreased following siTLR2 treatment in OGD-injured PC12 cells in the presence or absence of MSCs. Conclusions Our data indicate that TLR2 is involved in HIBD and that MSCs decrease apoptosis and improve learning-memory function in HIBD rats by suppressing the TLR2/NFκB signaling pathway via a feedback mechanism that reduces IL-10 release. These findings strongly suggest that MSC transplantation improves HIBD via the inhibition of the TLR2/NFκB pathway.